The business of culture : strategic perspectives on entertainment and media - Lampel, Joseph; Shamsie, Jamal; Lant, Theresa K. (Series in organization and management., 2006)
Concerns the management of creativity and innovation. This book provides serious analysis of the cultural industries - media, entertainment, film, music, and the arts -from a business perspective. It covers as many industries as possible from many different perspectives. It is a useful primer on cultural industries for students and scholars.